Effects of metrical dissonance and expertise on perceived emotion in Schumann's Carnaval. (March 2021) - Sommer, Jessica; Simmons, Kimberly; Tan, Daphne
Numerous studies have investigated the effects of pitch structures on perceived emotion in music, but the emotional effects of rhythm and meter have received far less attention. In the experiment reported here, we manipulated the metrical framework of music by Robert Schumann and asked participants to judge perceived emotion in the resulting excerpts. The distinction between metrical dissonance and consonance offered by Harald Krebs (1999) was the theoretical basis of this study. Stimuli were 10 metrically dissonant excerpts from Schumann's Carnaval and 10 metrically consonant recompositions of these excerpts. Recompositions maintained original tempi, global meters, and harmonic frameworks. Participants—graduate-level pianists and non-musicians—heard all 20 excerpts in randomized order. On each trial, they chose a cluster of emotion words, based on Schubert (2003), that best described the excerpt, a cluster that worst described the excerpt, and rated their level of interest. Results indicate significant effects of both metrical character and expertise on perceived emotion. There were also significant differences in the likelihood of participants changing their responses between metrically dissonant and consonant versions as a function of musical excerpt. This last finding leads to suggestions for future investigations on degrees of metrical dissonance.